Simultaneous bidirectional hindlimb locomotion in decerebrate cats - Lyakhovetskii, V. (Sci Rep, 2021)
We show that epidural spinal cord stimulation can elicit stable bidirectional locomotion of decerebrate cats on a split-belt treadmill. The stepping pattern of one limb was similar to unidirectional forward walking and, the other—was similar to unidirectional backward walking. This confirms that spinal and brainstem circuitry are sufficient to control such complex and extraordinary motor tasks driven by somatosensory input. Interlimb coordination during forward and backward walking was preserved in 2 out of 4 animals during ‘extreme’ conditions when one of the treadmill belts was stopped. Bidirectional locomotion worsened but was still possible after temporary spinalization by cooling the spinal cord on a low thoracic level. These present evidence for the great degree of the automatism for this stepping mode defined by the spinal neuronal networks.